Epidemiological profile analysis and incidence of yellow fever in Brazil (Research, Society and Development, 2020)
Yellow fever is an arbovirus produced by a Flavivirus, family Flaviviridae. The disease is endemic and enzootic in several tropical regions of the Americas and Africa. Objective: To describe the epidemiological profile of reported cases of yellow fever in the Brazilian population between 2010 and 2019 from a careful analysis of data obtained from the epidemiological databases of the Ministry of Health. Data analysis of the Brazilian Health System was performed. Reporting Disease Information (SINAN), and epidemiological data reported by the Ministry of Health, the variables evaluated were: country regions, age group, gender, disease evolution, in timeframe from 2010 to 2019. The incidence of cases yellow fever in Brazil, according to epidemiological records notified by the Ministry of Health, pointed to a high upward trend from 2016 to 2018, with higher incidence rates in the Southeast and Midwest regions, although there was a significant increase in notifications in other regions of the country. Statistically significant differences were found between genders, being the male sex most affected by the disease, and in relation to the age group most affected, we identified the young population between 20-59 years. Therefore, yellow fever presented itself as an important public health problem in the country, with active transmission and persistence of foci of transmission, requiring greater attention to this disease and its alarming risks. It is important to highlight the relevance of vaccines, and medicines that can fight the virus.